THE POETICS OF TRAVEL WRITING IN SUMINTO A. SAYUTI’S POETRY ANTHOLOGY KETIKA DIRI ADALAH KEPULANGAN DAN KEBERANGKATAN (2023) - Ilma, Awla Akbar; Wiyatmi, Wiyatmi; Hakim, Arif Rohman; Ridho, Muhammad Rasyid (Prosiding Konferensi Internasional Kesusasteraan, 2025)
This study analyzes the construction of travel poetry in Ketika Diri adalah Kepulangan dan Keberangkatan (2023) by Suminto A. Sayuti. Different from most studies of travel writing which tend to analyze travel in prose, this study shows poetry, with its dense and metaphorical aspects, is able to interpret both physical and spiritual travel in complicated ways. This study uses the theory and method of travel writing, focusing on the analysis of narrative constructions, including spatial description, temporal sequence, symbolism, and the meaning of the journey. The sample of this research consists of four poems: “Malam Malang”, “Dari Semarang”, “Malam Ngawi”, and “Sura-madu”. The analysis finds that the texts use both objective and subjective spatial representations. However, subjective representations show greater dominance as they tend to represent the reflective and emotive experiences of the lyrical self. The representations of reflection also depict travel as a metaphor of life, which is fleeting, while invoking a religious dimension. Thus, these travel-poems narrate the experience of geographical travels while expressing, in complicated fashion, the dynamics of the inner self, the meaning of self and the essence, self-meaning, and the essence of life.